Assessment of efficiency of local anesthesia for teeth extracting with use of mental anesthesia by S. Malamed and anesthesia of intraosseal part of the mental nerve from the point of view of the personal patient features (LLC "Endo Press", 2020)
Nowadays pain and anesthesia problems in dentistry are still actual. More than 40 techniques of local anesthesia on the mandible known today don't solve that problem, especially in the lateral part of the mandible. Our clinical experience and scientifical abstracts show low efficiency of the mental anesthesia by S. Malamed that, in our opinion, explained by absence of the accounting of specific features of anatomy of mental area and topography of nerves. The aim of the research was the assessment of efficiency of local anesthesia for teeth extracting with use of mental anesthesia by S. Malamed and anesthesia of intraosseal part of the mental nerve from the point of view of the personalized approach. Material and methods: 450 patients took part in research aged from 18 till 70 years during 2011-2013. Selection was representative. For carrying out local anesthesia concerning teeth extracting at a necrosis of a pulp (K041) and chronic apical periodontitis (K045) used dental syringe and also 3% of mepivacain and 4% of 1:200000 articain local anesthetics. The dosage in all cases was identical and made 0,6-0,7 ml. As a result of research clinical efficiency and safety of application during anesthesia of the intraosseal part of the mental nerve was proved during premolars extracting in surgical dentistry concerning necrosis of a pulp and chronic apical periodontitis.